Current Generation in Double-Matrix Structure: A Theoretical Simulation - Bogdan Lukiyanets; Dariya Matulka; Ivan Grygorchak (Nanomaterials and Nanotechnology)
Peculiarities of kinetic characteristics in a supramolecular system, in particular, in a double‐matrix structure observed at change of the guest content in a matrix‐host are investigated. Results obtained within the framework of a time‐independent one‐dimensional Schrödinger equation with three barrier potential qualitatively explain experimental data. They indicate the importance of size quantization of a system, correlation between energy and geometric characteristics of both guest and host in this case.